Pendampingan Orang Tua Menggunakan Filial Therapy dalam Meregulasi Emosi Saat Mendampingi Anak Belajar di Rumah - Indaria Tri Hariyani; Norma Diana Fitri; Mira Pradipta Ariyanti; Soemarmi Soemarmi (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
The aim of this research is to determine the assistance of parents using child therapy in regulating emotions when accompanying children to study at home. This research was conducted at the homes of 3 families who had children aged 4-7 years and the parents could not control their emotions when accompanying their children to study at home. The object of this research is parental assistance in the child's learning process at home. The data collection techniques used were observation, interviews and image documentation. The research method using data analysis is an interactive model. The research results showed that by being given Filial Therapy treatment, namely regulatory skills, setting boundaries, attentive listening, and focused play with children for 1 month, the informants were able to carry out Filial Therapy in a flexible and integrated manner. By applying Filial Therapy skills, parents become better able to regulate emotions, namely by reassessing cognitive and expression abilities. The assistance provided by parents is through filial therapy, parents accompany children to play and are directly involved in the game, there must be communication with parents, children are given the freedom to play, so that it will regulate parents' emotions in accompanying children to study at home.